Funding Hepatitis C Treatment in Correctional Facilities by Using a Nominal Pricing Mechanism. (January 2019) - Spaulding, Anne C.; Chhatwal, Jagpreet; Adee, Madeline G.; Lawrence, Robert T.; Beckwith, Curt G.; von Oehsen, William
The cost of treating all incarcerated people who have hepatitis C with direct-acting antiviral agents (DAAs) greatly stresses correctional facility budgets. Complex federal laws bar pharmaceutical companies from simply discounting expensive medications to prices that facilities can afford. This article discusses means by which correctional facilities may qualify under federal law as "safety-net providers" to allow sale of DAAs at a price <10% of the average manufacturer price (AMP). No new laws would need to be enacted to implement this strategy. Using fiscal year 2018 pricing data from the Georgia Department of Corrections, we derived an estimate for the AMP and then used this estimate to calculate a nominal price. The United States would save ∼$3 billion if manufacturers sold DAAs at a nominal price to correctional facilities. Use of this strategy would help solve the conundrum of how state and county governments can pay for hepatitis C treatment and would ultimately save money for society.